REPRESENTASI MOTIF BATIK LUKIS DI NEGERI PAHANG: SATU KAJIAN LITERATUR - Ramli, Sharulnizam; Musa Kahn, Sabzali; Yaacob, Mohd Nuri (Jurnal Pengajian Melayu (JOMAS), 2018)
Malaysian society is familiar with batik produced in Kelantan and Terengganu states, but very little is known about batik from Pahang, which is revered for its traditional ‘tenun Pahang’ (Pahang woven fabric). The reason for this lack of understanding regarding the uniqueness of batik lukis (hand drawn batik) from Pahang is that much information about it offers only general descriptions. This research is a qualitative study of literature that explores the process of producing Pahang’s batik lukis from perspectives of idea generation, the practitioners, cultural expressions and representation, the environment, and creativity and aesthetics, in order to delve deeper into a Malay art heritage worthy of preservation. Keywords: batik lukis, batik motifs, arts, culture.